AARS and CACNA1A mutations: diagnostic insights into a case report of uncommon epileptic encephalopathy phenotypes in two siblings - Romero, Vanessa I.; Sáenz, Samantha; Arias-Almeida, Benjamín; DiCapua, Daniela; Hosomichi, Kazuyoshi (Frontiers in Neurology, 2024)
Epilepsy, characterized by recurrent seizures, impacts 70-80% of patients, leading to cognitive deficits. The intricate relationship between seizure control and cognitive impairment remains complex. Epileptic encephalopathy (EE), an intensified form often rooted in genetic factors, is detectable through next-generation sequencing, aiding in precise diagnoses, family counseling, and potential treatment strategies. We present a case involving two sisters with refractory generalized seizures evolving into dysarthria, dysphagia, ataxia, and cognitive decline. Despite normal physical exams, abnormal electroencephalogram results consistent with epilepsy were noted. Whole Exome Sequencing identified heterozygous variants in the alanyl-tRNA synthetase (AARS) and Calcium Voltage-Gated Channel Subunit Alpha 1 (CACNA1A) genes. The AARS variant (c.C2083T, p.R695*) was maternal, while the CACNA1A variant (c.G7400C, p.R2467P) was paternal. Patients A and B exhibited a unique blend of neurological and psychiatric conditions, distinct from common disorders that begin adolescence, like Juvenile Myoclonic Epilepsy. Whole Exome Sequencing uncovered an AARS gene and CACNA1A gene, linked to various autosomal dominant phenotypes. Presence in both parents, coupled with familial reports of migraines and seizures, provides insight into accelerated symptom progression. This study underscores the importance of genetic testing in decoding complex phenotypes and emphasizes the value of documenting family history for anticipating related symptoms and future health risks.